Water service valuation in tidal lowland agriculture - Muhammad Yazid,; Shamsudin, Mad Nasir; Abdul Rahim, Khalid; Radam, Alias; Muda, Azizi (Universiti Putra Malaysia Press, 2015)
Water service is a key factor in tidal lowland agriculture where water supply fluctuates following the tidal cycle. Under controlled situations, water can be properly supplied to farmland based on crop water requirements through proper operation and maintenance of the tidal irrigation system. This study aimed at estimating the value of water service in order to support the implementation of a water service fee. The benefit from water service is compared to a water service fee estimated from the cost of water distribution. To achieve the objective, the study employed production function estimation with rice as the main crop. Data were collected through a field survey on randomly selected farmers at Telang Delta, the rice production centre for tidal lowlands of South Sumatra, Indonesia. The result indicates that the value of water service in rice production is higher than any estimates of a water service fee. Proven to be a significant determinant of rice production, it has been suggested that water service should obtain financial support from farmers who benefited from available water service.